Caveat Emptor: Predatory Publishers, Rogue Journals, and the Potential Corruption of Addiction Science. - Babor, Thomas F.; Ward, Judit H. (Journal of Studies on Alcohol & Drugs, 2018)
The name predatory publisher has been applied by academic librarian Jeffrey Beall to describe an open-access, scholarly publishing business model in which publication fees are charged to authors without providing the editorial judgment, peer-review process, and publishing services associated with more established journals. In the addiction field, as many as 20 journal titles now operate according to this model, and most of their editors are either nonexistent or impossible to contact. Although predatory publishing should not be equated with open access, this article argues that predatory publishers are diluting scientific quality in the addiction field by taking advantage of the open-access movement. Beyond the damage done to the reputations of naive authors and figurehead editorial board members, there is a cascade of effects resulting from the shabby publication process itself. If the addiction field is to be protected from predatory publishers, all sectors need to be involved. Declarations of "buyer beware" and "the emperor has no clothes" are just the first steps in a process of preventing further damage to the integrity of addiction science. As described in this article, concerted action will be required by authors, editors, and professional societies.